Creativity and its discontents : China's creative industries and intellectual property rights offenses - Pang, Laikwan (Duke University Press, 2012)
Laikwan Pang offers a complex critical analysis of creativity, creative industries, and the impact of Western copyright laws on creativity in China.
Keywords: Creative ability -- Economic aspects -- China.; Cultural industries -- China.; Intellectual property infringement -- China.; Intellectual property -- China.; Law and economic development.; Industries culturelles -- Chine.; Créativité -- Aspect économique -- Chine.; Propriété intellectuelle -- Chine.; Infractions à la propriété intellectuelle -- Chine.; Droit et développement.; Copyright law.; ART -- Business Aspects.; Creative ability -- Economic aspects; Cultural industries; Intellectual property; Intellectual property infringement; Law and economic development; China